Evaluation Of The Perception And Effectiveness Of Calendar Blister Pack Intervention On Medication Adherence And Clinical Outcome Among Hypertensive Patients At Kulim Hospital, Malaysia. A Mixed Methodology Approach - Tan, Bee Ying (2018)
This study aimed to explore patients’ perception on medication packaging and calendar blister pack (CBP), to assess the effectiveness of CBP intervention towards medication adherence, clinical outcome (blood pressure) as well as the cost associated with the said intervention among hypertension patients in Kulim Hospital, Malaysia. A mixed methodology approach which involved both qualitative and quantitative methodology were implemented in this study. In phase I study, two focus group discussions were conducted among 16 hypertensive patients to collect data on patient’s perception towards medication packaging and CBP medications in managing hypertension. Collected data were transcribed verbatim and analysed by thematic analysis to identify the emerging themes. Phase II in this study was designed as a randomized controlled trial with the study outcomes were medication adherence, blood pressure level and treatment costs which included costs for prescribed medications, clinic visit, hospitalization, medical procedure and diagnostic test.